Card games: daily resistance in Rute (Córdoba) in the second half of the 18th century - Clavio Sanchez (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
In the Provincial Historical Archive of Cordoba has recently registered the transfer of a documentary section of civil justice from Rute. The value of the information referring to quotidian life in this village is extraordinary and among the multiple practices described as crime we have selected the card games for the interest of the interrelation norm-practice-representations, the participation of all social groups, the exhibition in public and private spaces, etc. The result is a polyhedral mosaic in which fun, transgressions and quotidian resistances are intertwined in a town in movement, and in which the illustrated reformist dispositions become blurred by the pulse between leisure and legislation.